Pattern of inter-marriage in Keningau: a preliminary study towards religious tolerance - Suraya Sintang (2016)
This paper seeks to discuss the profiling pattern of inter-marriage among the Keningau community and how the inter-marriage can be a social indicator towards the practice of religious tolerance. This has been done through analyzing the quantitative data collected randomly from some folk villages in Keningau. The concept of inter-marriage as discussed in this paper broadly means inter-marriage between different ethnic groups, inter-faith marriage between different religions and inter-faith marriage that leads to conversion to Islam. The findings show that there are some cases or incidents whereby the inter-faith marriage happened to be the couples from Muslim and non-Muslim. The other findings to be discussed in which the inter-marriage is concerned are mixed-faith family (one family different religion), conversion to other religion and inter-faith marriage among the siblings and relatives. Therefore, the study shows that most of the respondents gain positive experience either involve inter-ethnic or inter-religious relation which leads to their good response on the readiness to get marriage with other religion and do not feel hesitate in attending family meal from other religion. The findings conclude that the profiling pattern of inter-marriage in Keningau is very encouraging sign towards religious tolerance as inter-marriage seems acceptable by the respondents involved in this study.